Proses Cognitive Defusion Pada Mahasiswa Pemilih Pemula Dalam Menghadapi Black Campaign Di Media Sosial - Achmed Shodiqin; Aldino Permana; Muhammad Iqbal Jazuli; Ocvin Dwi Pangga; Reno Aryandi; Khoiriya Ulfah (CV. ITTC INDONESIA, 2026)
This study uses a descriptive qualitative method to analyze the cognitive defusion process among first-time voters in facing social media black campaigns. Using purposive sampling, four active students from Universitas Islam Negeri Raden Intan Lampung were selected as informants. Data were gathered through semi-structured in-depth interviews and analyzed using an interactive model. The results indicate that exposure to black campaigns triggers initial emotional arousal, including shock, annoyance, and anger. However, informants successfully avoided cognitive fusion through cognitive defusion mechanisms by maintaining cognitive distance and suspending belief. This condition stimulated adaptive self-regulation strategies such as distraction or taking a timeout. Ultimately, this psychological stability encouraged the execution of committed action, specifically independent data verification through official sources to maintain political objectivity.